Characterization of biofilm formation and multi-drug resistance among Pseudomonas aeruginosa isolated from hospital wastewater in Dhaka, Bangladesh - Md Abu Sayem Khan; Zahidul Islam; SM Tanjil Shah; Sabita Rezwana Rahman (IWA Publishing, 2024)
Hospital wastewater has been identified as a hotspot for the emergence and transmission of multidrug-resistant (MDR) pathogens that present a serious threat to public health. Therefore, we investigated the current status of antibiotic resistance as well as the phenotypic and genotypic basis of biofilm formation in Pseudomonas aeruginosa from hospital wastewater in Dhaka, Bangladesh. The disc diffusion method and the crystal violet assay were performed to characterize antimicrobial resistance and biofilm formation, respectively. Biofilm and integron-associated genes were amplified by the polymerase chain reaction. Isolates exhibited varying degrees of resistance to different antibiotics, in which >80% of isolates showed sensitivity to meropenem, amikacin, and gentamicin. The results indicated that 93.82% of isolates were MDR and 71 out of 76 MDR isolates showed biofilm formation activities. We observed the high prevalence of biofilm-related genes, in which algD+pelF+pslD+ (82.7%) was found to be the prevalent biofilm genotypic pattern. Sixteen isolates (19.75%) possessed class 1 integron (int1) genes. However, statistical analysis revealed no significant association between biofilm formation and multidrug resistance (χ2 = 0.35, P = 0.55). Taken together, hospital wastewater in Dhaka city may act as a reservoir for MDR and biofilm-forming P. aeruginosa, and therefore, the adequate treatment of wastewater is recommended to reduce the occurrence of outbreaks. HIGHLIGHTS A high occurrence of P. aeruginosa was observed in hospital effluents.; 93.82% of isolates were multidrug-resistant.; Most of the isolates showed biofilm formation activities.; 19.75% of isolates harbored class 1 integron genes.; Hospital wastewater in Dhaka acts as a reservoir of MDR P. aeruginosa.;